Graphene Quantum dots for Biophotonic Applications. Issue 1786 (26th August 2015) - Tilwani, Aneshkumar; Bell, Hildegarde; Alvarez, Jose; Naqshbandi, Belqais; Erogbogbo, Folarin
ABSTRACT: Graphene Quantum Dots (GQDs) are of interest to the biomedical community due to their unique fluorescence properties, which may be advantageous for biology and medicine. Advantages of this graphene nanomaterial over fluorescent dyes for biomedical imaging include bright emission, easy surface modification, biocompatibility, and anticipated low toxicity. We hypothesize that GQDs with desirable fluorescence properties which can be used for effective biomedical imaging (such as near infrared emission) may be synthesized from cheap carbon sources. Here, we show that these fluorescent GQDs are fabricated in a facile wet chemistry route using activated charcoal as the starting material. The GQDs were characterized with AFM, TEM, FTIR, PL spectroscopy, Raman spectroscopy and animal imaging techniques. The particles were visible in animals indicating their potential for biomedical imaging. The GQDs exhibited excitation that spanned the UV and visible ranges and emission that spanned the visible and near infrared ranges. The GQDs were an average of 4 nm in height, crystalline, from 1 to 60 nm in size. The GQDs were consistent with the presence of graphene and the following functional groups: C-O, C-H, C=C, and CO2 H. In conclusion, GQDs with favorable photophysical properties can be produced from affordable and widely available raw materials for imaging and other biomedical application purposes.